Community forests, carbon sequestration and REDD+: evidence from Ethiopia. (28th September 2015) - Beyene, Abebe D.; Bluffstone, Randall; Mekonnen, Alemu
Abstract: REDD + is one of the tools under development to mitigate climate change, but it is not yet clear how to appropriately bring in the approximately 25 per cent of developing country forests that are managed by communities. Drawing on the economics of collective action literature, the authors attempt to shed light on whether forest collective action itself sequesters carbon. Using satellite imagery combined with household and community data from Ethiopia, they examine whether community forests (CFs) with high levels of collective action attributes known to be associated with better management have more carbon than other systems. Although these results should be considered indicative due to the nature of the data, the analysis suggests that in the absence of dedicated sequestration policies the quality of local-level collective action offers at best marginal carbon benefits. Specific incentives like REDD + may therefore play important roles in delivering climate change benefits from CFs in low-income countries.